Optimal distance of an external focus of attention in standing long jump performance of athletes - Gh. Lotfi (Physical Education of Students)
Background and Study Aim: Recently, studies have shown that an external focus of attention improves the performance of individuals. Some studies have also confirmed the superiority of distances away from body for external focus of attention. The aim of this study was to determine the optimal distance of an external focus of attention when performing athletes' standing long jump.